Effects on Photosynthetic Response and Biomass Productivity of Acacia longifolia ssp. longifolia Under Elevated CO2 and Water-Limited Regimes - Javaid, Muhammad Mansoor; Wang, Xiukang; Florentine, Singarayer K.; Ashraf, Muhammad; Mahmood, Athar; Li, Feng-Min; Fiaz, Sajid (Frontiers in Plant Science, 2022)
It is known that the impact of elevated CO2 (eCO2) will cause differential photosynthetic responses in plants, resulting in varying magnitudes of growth and productivity of competing species. Because of the aggressive invasive nature of Acacia longifolia ssp. longifolia, this study is designed to investigate the effect of eCO2 on gas exchange parameters, water use efficiency, photosystem II (PSII) activities, and growth of this species. Plants of A. longifolia ssp. longifolia were grown at 400 ppm (ambient) and 700 ppm (elevated) CO2 under 100 and 60% field capacity. Leaf gas exchange parameters, water use efficiency, intrinsic water use efficiency, instantaneous carboxylation efficiency, and PSII activity were measured for 10 days at 2-day intervals. eCO2 mitigated the adverse effects of drought conditions on the aforementioned parameters compared to that grown under ambient CO2 (aCO2) conditions. A. longifolia, grown under drought conditions and re-watered at day 8, indicated a partial recovery in most of the parameters measured, suggesting that the recovery of this species under eCO2 will be higher than that with aCO2 concentration. This gave an increase in water use efficiency, which is one of the reasons for the observed enhanced growth of A. longifolia under drought stress. Thus, eCO2 will allow to adopt this species in the new environment, even under severe climatic conditions, and foreshadow its likelihood of invasion into new areas.